Assessing Value for Money: the Oxford Policy Management Approach - King, Julian (Oxford Policy Management, 2023)
This document offers practical guidance for assessing the Value for Mo ney (VfM) of government- and donor-financed programmes and policy inte rventions. In line with OPM’s focus and mission, it has been predomina ntly applied in the international development sector, but the approach upon which it is based is also used in the context of domestic public policy and programmes.1 There is increasing scrutiny on VfM in intern ational development, but a lack of appropriate methods to support its assessment. There is a risk of reaching invalid conclusions if VfM eva luation is tied to a narrow set of indicators devoid of any evaluative judgement—for example, by emphasising the most readily quantifiable m easures rather than the most important (but harder to quantify) aspect s of performance, or by focusing on the quantification of outputs and outcomes at the expense of more nuanced consideration of their quality , value, and importance. The approach presented in this guide combines theory and practice from evaluation and economics to respond to requi rements for accountability and good resource allocation, as well as to support reflection, learning, and adaptive management. It involves de veloping and implementing a framework for: • organising evidence of pe rformance and VfM; • interpreting the evidence on an agreed basis; and • presenting a clear and robust performance story. This guide sets ou t a framework for making and presenting judgements in a way that opens both the reasoning process and the evidence to scrutiny. The approach is designed to be used in alignment with broader monitoring, evaluati on, and learning (MEL) systems—both for efficiency's sake, and to ensu re conceptual coherence between VfM evaluation and wider MEL work. The VfM framework achieves these aims by: • using explicit criteria (aspe cts of performance) and standards (levels of performance) to provide a transparent basis for making sound judgements about performance and V fM; • combining quantitative and qualitative forms of evidence to supp ort a richer and more nuanced understanding than can be gained from th e use of indicators alone; • accommodating economic evaluation (where feasible and appropriate) without limiting the analysis to economic me thods and metrics alone; and • incorporating and building on an approa ch to VfM evaluation which is familiar to international aid donors.